2014
DOI: 10.1002/prep.201400079
|View full text |Cite
|
Sign up to set email alerts
|

Performance Assessment of Some Isomers of Saturated Polycyclic Hydrocarbons for Use as Jet Fuels

Abstract: The performance of jet fuel depends on the density (ρ), condensed phase heat of formation (▵fH°(c)), and specific impulse (ISP). Exo‐tricyclo[5.2.1.0(2,6)]decane (C10H16) or JP‐10 is now used as a suitable synthetic liquid jet fuel because it has the approximated values of ρ=1.1 g cm−3 and ▵fH°(c)=− 123 kJ mol−1 and a broad range between the melting and boiling points, i.e. Tbp–Tmp=196.2 K. This work introduces a suitable pathway for calculation of the values of ρ, ▵fH°(c), and ISP of 13 well‐known isomers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The M06‐2X functional is a modern hybrid density functional on top of meta‐GGAs. It has been shown to be superior for the description of non‐covalent interactions, which is of great significance for a good description of PSHs. Indeed, M06‐2X significantly improves over B3LYP as shown in Tables and .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The M06‐2X functional is a modern hybrid density functional on top of meta‐GGAs. It has been shown to be superior for the description of non‐covalent interactions, which is of great significance for a good description of PSHs. Indeed, M06‐2X significantly improves over B3LYP as shown in Tables and .…”
Section: Resultsmentioning
confidence: 99%
“…), which contains three fused five‐membered rings. It has been anticipated that the energy characteristics of the hydrocarbon propellants can be further enhanced by introducing fused or caged hydrocarbons containing three‐ and four‐membered rings . This necessitates accurate calculations of HOFs for PSHs.…”
Section: Introductionmentioning
confidence: 99%
“…The multiple linear regression method [29] was used to find the optimized model as: give increasing and decreasing functions in the triazolium-based EISs, respectively. For the design of high detonation or combustion performance compounds, it is desirable to choose those materials with high positive heats of formation [3,[5][6][7][8][9][10]30]. Coefficients in Equation 1 show the contributions of the different variables for obtaining a high heat content in triazolium-based EISs.…”
Section: Deriving the New Modelmentioning
confidence: 99%
“…The condensed phase heat of formation [D f H8(c)] of an energetic compound at 298.15 K. It is an essential input pa- 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 rameter to assess performance properties of explosives and propellants such as heat of detonation [29] and power [30]. Higher positive value of D f H8(c) provides higher heat of combustion [31] and energy level of the molecule [32] as well as higher released energy upon detonation and detonation temperature [5,33,34]. For high nitrogen content energetic compounds with general formula C a H b N c O d , it was found that the optimized correlation can be given as [35]: where D f H8(c) is in kJ mol À1 ; IF and DF are two variables the presence of amino groups (ÀNH 2 ) contributes in DF can reduce the value of D f H8(c).…”
Section: Condensed Phase Heat Of Formationmentioning
confidence: 99%